PERBANDINGAN INDEKS ERODIBILITAS TANAH YANG DITETAPKAN DENGAN METODE WISCHMEIER DAN RAINFALL SIMULATOR - Sena Rizki Triyudanto; Zaenal Kusuma; Istika Nita (Jurnal Tanah dan Sumberdaya Lahan, 2021)
Land use in the upstream area of the Brantas watershed, including that inÂ  Tawangsari village, Pujon District of Malang Regency, has undergone significant changes. The conversion of forest to moor, plantations, and settlements has resulted in decreased soil quality leading to soil degradation. The purpose of this research was aimed to compare the soil erodibility index determined by the rainfall simulator with Wischmeier methods. The results showed that there was a relationship between the results of the soil erodibility value using the Wischmeier method with land use and slopes based on the correlation and regression values caused by the physical properties of the soil. There were differences in soil erodibility index with the Wischmeier method and the Rainfall Simulator method, namely the average agroforestry results of 0.108 and 0.112 and an average of 0.152 and 0.147 moor. The use of the Wischmeier method is more recommended.